6 Laws of New Hampshire, Second Constitutional Period 84-85 (N.H. Sec'y of State ed., 1917) - (:unkn) unknown (My University, 1792)
The militia consisted of "every free, able bodied white male citizen of this State resident therein who is, or shall be of the age of eighteen years and under the age of Forty years. Commissioned officers had to have "a pair of Pistols, the holsters of which to be covered with bear-skin Caps." Commissioned officers might have an espontoon, but field officers would not. Again, "parents, Masters, or Guardians" had to furnish their charges with "Arms and Accoutrements." And again they were "liable for the neglect and non appearance of such persons . . . under their care.
Keywords: MILITIAS